VERBAL POLITENESS IN LANGUAGE TEACHING EUROPEAN REFERENCE DOCUMENTS - Pilar Robles Garrote (Modulema, 2019)
Knowing the intercultural particularities of verbal politeness is essentialto achieve an adequate development of communicative competenceand good social relations through interaction with people from othercultures. Thus, it is not strange that language teaching referencedocuments such as the Common European Framework of Referencefor Languages, the Reference Framework for the Plural Approachesof Languages and Culture or the Plan Curriculum of the CervantesInstitute all refer to the appropriate use of pragmatic strategies of verbal politeness. This article highlights the contribution of theseEuropean reference documents to the teaching-learning of effectivestrategies for the appropriate use of verbal politeness in interculturalcontexts.